Etiology and Outcome of Status Epilepticus - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The etiology and outcome of status epilepticus (SE) in 135 children (76 boys, 59 girls), ages 1 month to 15 years, admitted to Nemazee Hospital, Shiraz, Iran, between 1999 and 2004, were studied retrospectively, and outcomes were rated according to the Glasgow Outcome Score (GOS).